2020
DOI: 10.1080/19336896.2020.1857038
|View full text |Cite
|
Sign up to set email alerts
|

Experimental oral transmission of chronic wasting disease to sika deer (Cervus nippon)

Abstract: Chronic wasting disease (CWD) affects a broad array of cervid species and continues to be detected in an expanding geographic range. Initially introduced into the Republic of Korea through the importation of CWD-infected elk (Cervus canadensis), additional cases of CWD were subsequently detected in farmed Korean elk and sika deer (Cervus nippon). Wild and farmed sika deer are found in many regions of Asia, North America, and Europe, although natural transmission to this species has not been detected outside of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In 2001, epidemiological investigations confirmed that CWD was introduced to the Korean peninsula by captive elk (Cervus elaphus nelsoni), imported from Canada in 1994 and 1997 [30,31]. CWD was subsequently detected in farmed elk populations in 2001,2004,2005,2010 and 2016 and since no evidence of natural CWD transmission to sika deer has been documented [32]. In other countries, CWD was not reported until 2016.…”
Section: Cwd Epidemic In North Americamentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, epidemiological investigations confirmed that CWD was introduced to the Korean peninsula by captive elk (Cervus elaphus nelsoni), imported from Canada in 1994 and 1997 [30,31]. CWD was subsequently detected in farmed elk populations in 2001,2004,2005,2010 and 2016 and since no evidence of natural CWD transmission to sika deer has been documented [32]. In other countries, CWD was not reported until 2016.…”
Section: Cwd Epidemic In North Americamentioning
confidence: 99%
“…If the E226 and Q226 alleles were equally present in the tested population in China and Korea, the G100 allele was only detected in 3% of the animals, in association with the E226 aa and only the Q226 allele was detected in Europe pure sika. Efficient oral transmission of CWD from Elk to Sika deer was reported [32], but the potential impact of the above-mentioned allelic variations was not tested in this species.…”
Section: Cervus Nippon or Sika Deermentioning
confidence: 99%
“…Oral exposure is thus a plausible route of transmission of CWD prions for cervids in nature. In fact, oral inoculation has resulted in productive infections in moose (Kreeger et al 2006 ), elk (Hamir et al 2006 ; Plummer et al 2017 ), white-tailed and mule deer (Plummer et al 2017 ), red deer (Martin et al 2009 ; Balachandran et al 2010 ), sika deer ( Cervus nippon ) (Sohn et al 2020 ) and reindeer (Mitchell et al 2012 ). As further evidence to support the efficacy of oral infection and to track early CWD pathogenesis, an experimental study (Sigurdson et al 1999 ) was conducted employing mule deer fawns captured outside the CWD endemic region (Miller et al 2000 ; Miller and Williams 2003 ).…”
Section: Cwd Infection Progression From Exposure Intra-host Dissemination To Sheddingmentioning
confidence: 99%
“…Transmissible spongiform encephalopathies (TSEs) are a group of fatal, progressive neurodegenerative diseases that result from the misfolding and accumulation of endogenous prion protein (PrP Sc ) [1]. Transmissible and spontaneous prion diseases have been described in a wide variety of species including humans [2], sheep [3][4][5], goats [6], mink [7], cattle [8], white-tailed deer [9], mule deer [9], elk [9,10] camels [11], moose [12], reindeer [13], red deer [14], sika deer [15], cats [16], and various zoo species [17,18].…”
Section: Introductionmentioning
confidence: 99%